Tratamento físico-químico do caldo de cana produz cachaça de qualidade - Ribeiro, Mara Lucia Dias [UNESP]; Ferreira, Osania Emerenciano; Teixeira, Vitor [UNESP]; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (GN1 Sistemas e Publicacoes, 2017)
Cachaça is the spirit produced from the distillation of fermented sugarcane juice. It is currently the second most consumed alcoholic beverage in Brazil, and the third most-distilled drink in the world. Several factors negatively affect the production chain, including treatment of the juice and the yeast employed. The aim of this study therefore, was to evaluate the influence of the type of yeast and treatment on the quality of the distillate. The experiment was carried out during the 2014/2015 season, using the SP83-2847 variety of sugarcane. The experimental design was completely randomised into split lots with nine replications. The lots consisted of the type of treatment (clarified and non-clarified juice), and the sub-lots, of the types of yeast (Natural and CA-11). Chemical characteristics of the must were determined, such as Total Soluble Solids (TSS), Total Phenolic Compounds (CFT), Total Reducing Sugars (ART) and Total Acidity. During the fermentation process, the viability of the cells and shoots, and the sprouting index were evaluated. The SST, ARRT, pH, total acidity, alcohol content, glycerol and fermentation efficiency were determined in the sugarcane must. The composition of the cachaças was determined by quantification of total aldehydes, total esters, methanol, acrolein, ethyl carbamate, furfural, volatile acidity and congener coefficient. Electrical conductivity, turbidity and pH were also analysed, secondary components being determined by gas chromatography. Pre-treatment of the juice resulted in ideal conditions for the yeast. The CA-11 yeast showed higher levels of cell viability. The interaction between treatment and selected yeast, results in a cachaça of a more-balanced composition.
Physico-chemical treatment of sugarcane juice produces quality cachaça
Keywords: CA-11; Distilled beverage; Native yeast; Simple liming; Sugarcane